(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical characteristics of patients with low rectal adenocarcinoma who underwent laparoscopic sphincter-preserving surgery at Viet Duc University Hospital from 2018 to 2023. Subject and method: A totally of 49 patients diagnosed with rectal cancer who underwent laparoscopic sphincter-preserving surgery between January 2018 and December 2023 at Viet Duc University Hospital who were included in a retrospective descriptive study. Data were collected from medical records that met the inclusion criteria, archived at the hospital’s medical record storage department, and recorded into a standardized research case report form. Results: The most common preoperative clinical symptoms were mucus in stool (77.6%), altered stool shape (59.2%), and tenesmus (42.9%). Some patients also presented with frequent bowel movements (32.7%) and weight loss (28.6%). Conclusion: Symptoms such as rectal bleeding, abdominal pain, and tenesmus are the most prominent and alarming signs in patients with low rectal adenocarcinoma.